Ancestral Heritage Toward Health Innovation: A Study of the Antibacterial Activity of Betel Leaf (Piper betle Linn.) Extract from the Betel-Chewing Tradition Against Oral Pathogenic Bacteria - Norhidayah, Norhidayah; Maza, Safira; Anggraeni, Novita; Qurrahman, Taufik; Pratama, Rizki Rahmadi; Soemarie, Yulistia Budianti (Sciences of Pharmacy, 2026)
Traditionally, menginang (a mixture of betel leaf, areca nut, gambir, and lime) has been used as a natural antibacterial agent. This study aimed to compare the antibacterial activity of single betel leaf extract and menginang extract against four oral pathogenic bacteria in vitro. This study compared the antibacterial activity of traditional menginang extract and single betel leaf extract against multiple oral pathogenic bacteria to evaluate their potential synergistic antibacterial effects. The experimental method used a disk diffusion technique at three concentrations (12.5%, 25%, and 50%), and the data were analyzed using one-way ANOVA and Bonferroni post hoc tests. Chlorhexidine 0.2% was used as the positive control, while distilled water was used as the negative control. The 50% menginang extract showed the strongest antibacterial activity against all tested bacteria, with inhibition zones ranging from 22.76 ± 1.38 mm to 28.22 ± 0.14 mm, and the differences were statistically significant (p < 0.05). The inhibition zones produced by the 50% menginang extract were close to those of 0.2% chlorhexidine. The superiority antibacterial activity of menginang extract may be associated with synergistic interactions among alkaloids, phenolics, flavonoids, tannins, saponins, triterpenoids, and steroids identified during phytochemical screening. The menginang extract has high potential to be developed as an innovative natural product for oral health.